Small extracellular vesicles in breast cancer brain metastasis and the prospect of clinical application - Luo, Tingli; Kang, Yue; Liu, Yushi; Li, Jingyue; Li, Jianyi (Frontiers in Bioengineering and Biotechnology, 2023)
Extracellular vesicles (EVs) are nanoscale extracellular particles that have received widespread scientific attention for carrying a variety of biomolecules such as nucleic acids and proteins and participating in the process of intercellular information exchange, making them become a research hotspot due to their potential diagnostic value. Breast cancer is the leading cause of cancer-related death in women, approximately 90% of patient deaths are due to metastasis complications. Brain metastasis is an important cause of mortality in breast cancer patients, about 10-15% of breast cancer patients will develop brain metastasis. Therefore, early prevention of brain metastasis and the development of new treatments are crucial. Small EVs have been discovered to be involved in the entire process of breast cancer brain metastasis (BCBM), playing an important role in driving organ-specific metastasis, forming pre-metastatic niches, disrupting the blood-brain barrier, and promoting metastatic tumor cell proliferation. We summarize the mechanisms of small Evs in the aforementioned pathological processes at the cellular and molecular levels, and anticipate their potential applications in the treatment of BCBM, with the hope of providing new ideas for the precise treatment of BCBM.